Смертельные тайны: [роман] / Роберт Брындза - Брындза Роберт (Серия "Новый мировой триллер", 2022)
Экземпляры: ЦБ (20230508) / Инвентарный номер: 59905 / Цена: 537.57 / Сис.шифр: 84(4/8) / Авт.знак: Б 89 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44